Fatores preditivos de infecção em pacientes renais crônicos em uso de cateteres venosos centrais - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
PURPOSE: The purpose of this research was to determine the central venous catheter-related infection rate in a dialysis center from the state of Amazonas, as well as to identify risk factors and microbiological profile of the infections. METHODS: It was an observational study, with data collected in a prospective manner, through direct interviews with patients and monthly chart analysis of patients undergoing hemodialysis using central venous catheters in a dialysis center, over a 12-month period. RESULTS: 96 central venous catheters, in 48 patients, were analysed. Out of the total, 78 were non-tunnelized central venous catheters (81.3%) and 18 were tunnelized central venous catheters (18.7%), 53,1% of the catheters were exchanged because of infection, and blood cultures were obtained in 35,2% of patients that presented catheter-related infection. Regarding microbiological profile, among the blood cultures with bacterial growth (9), Gram-negative bacteria were isolated in five and Gram-positive bacteria were isolated in four cultures. The most commonly isolated bacteria was Staphylococcus hominis, in 22,2% of the positive blood cultures. CONCLUSION: The overall hemodialysis venous catheter infection rate was 10.1 episodes/1000 catheter days, of which, 15.1 occurred in non-tunnelized catheters and 3.3 episodes/1000 catheters days in tunnelized catheters. Predisposing factors of infection were the use of non-tunnelized catheter and 2 weekly hemodialysis sessions. Regarding the microbiological profile, over half of isolated bacteria were Gram-negative
Keywords: Hemodiálise - Complicações e sequelas; Hemodiálise - Pacientes; Rins - Doenças; CIENCIAS DA SAUDE: MEDICINA; Diálise renal; Infecções relacionadas a cateter; Cateteres de demora; Unidades hospitalares de hemodiálise